A comparison of interfacial testing methods and sensitivities to carbon fiber surface treatment conditions. (March 2019) - Stojcevski, Filip; Hilditch, Timothy B.; Henderson, Luke C.
Abstract: Studies show surface treatments improve interfacial adhesion of carbon fiber composites however little research examines the translatability of interfacial shear strength (IFSS) across testing scales. How surface treatments may influence IFSS translatability is also unclear. Investigation of this relationship is important to compare results between commonly used test methodologies. This paper evaluates the translatability and sensitivity of IFSS across micro-, meso- and macro-scale testing protocols. Tests investigated were single fiber fragmentation (SFFT), Iosipescu and short beam shear (SBS) testing. Twelve pristine fibers were produced using a combination of three electrochemical oxidation amperages (0 A, 2 A and 3.4 A) and four sizing ratios (unsized, 1:10, 1:15 and 1:20 parts epoxy:water). Results show differences between micro, meso and macroscale IFSS, especially for unsized fibers and when sizing emulsion ratio is the independent variable. As oxidation amperage and sizing levels were increased, the disparity in IFSS values across testing scales decreased.